J roberts 21807 if we convolve g n x n znxn gn y

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: yn k= hn xn D.2.3 hn Distributivity Property If we convolve x n with the sum of y n and z n we get xn (y n +z n )= xk k= (y n k +z n k ) or xn (y n +z n )= xkyn k+ k= =x n Therefore xn (y n +z n xkzn k . k= )= x =x n yn n D-5 y n +x n zn zn. M. J. Roberts - 2/18/07 D.2.4 Differencing Property Let y n = x n h n . Using the time-shifting property y n n0 = x n h n n0 = x n n0 hn the first backward difference of their convolution sum is y n 1 =x n yn hn xn hn 1 or yn yn 1= xmhn m m= xmhn m 1. m= Combining summations, yn 1= yn ( xm hn m m= or yn D.2.5 (h y n 1 =x n n hn m 1 hn 1 ) ) Sum Property Let y n = x n h n and let the sum of all the impulses in the functions y, x, and h be S y , S x and S h , respectively. Then yn= xmhn m m= and Sy = yn= n= xmhn m. n= m= Interchanging the order of summation, Sy = xm m= n= h n m = Sx Sh . = Sx = Sh D-6...
View Full Document

This note was uploaded on 02/11/2014 for the course EECS 320 taught by Professor Philips during the Spring '06 term at University of Michigan.

Ask a homework question - tutors are online